Bis(diphenylphosphinyl)-functionalized dipyrido-annulated NHC towards copper(i) and silver(i). Issue 32 (24th July 2019) - Zhang, Sihan; Shang, Rong; Nakamoto, Masaaki; Yamamoto, Yohsuke; Adachi, Yohei; Ohshita, Joji
Abstract : Sterically rigid bis(phosphinyl)dipyrido-annulated NHC coordinates with Ag(i ) and Cu(i ) centres to form luminescent multinuclear complexes. Abstract : The coordination chemistry of our recently isolated bis(diphenylphosphinyl)-functionalized dipyrido-annulated NHC (N-heterocyclic carbene), dpa P2 -NHC, towards copper(i ) and silver(i ) has been studied. Based ondpa P2 -NHC, two dinuclear silver and copper complexes [2, (Ag2 L2 ) and3, (Cu2 L2 )], two tetranuclear copper complexes 4, [Cu4 L2 (NCMe)2 ] and6, (Cu4 LBr4 ) and a pentanuclear copper complex [5, (Cu5 L2 Br3 )] exhibiting strong intramolecular metal–metal interactions were achieved and characterized. All the complexes exhibited dynamic behavior in solution, in which the NMR coalescence of2 was well resolved at low temperature (below 208 K) and dissociation for2 was observed according to the calculated Eyring plot.Ag2 L2 (2 ) shows a similar coordination sphere to that of our previously reported gold complexAu2 L2 ;Cu2 L2 (3 ) features a rare μ2 -bridging carbene and a terminal carbene; Cu4 LBr4 (6 ) is neutral and monomeric, in which four copper atoms were rigidly fixed by the tridentatedpa P2 -NHC ligand and bromide anions. All the complexes (2–6 ) were luminescent at room temperature, in which4–6 provided phosphorescence at 77 K. Based on the comparison of the emission bands withdpa P2 -NHC, we conclude that the electronic transitions of2–6 can be attributed to the ligand-centered (LC) transitions.